Post-Pandemic Covid-19: Factors Affecting Startup Success in the Indonesian Economy - Ratih Damayanti; Andrie Yuswanto; Ahmad Hariri (East Asian Journal of Multidisciplinary Research, 2022)
This study aims to analyze the factors that influence the success of startups in helping the government increase economic growth during the Covid-19 pandemic. The Covid-19 pandemic had significantly impacted the economy, including Indonesia. Therefore, a solution is needed to improve the Indonesian economy. The variables in this study are "Strategy", "Innovation", "Experience", "Economic Growth", and as an intermediate variable, "Startup Success". Two hundred seventeen valid respondents are online business owners who answered the questionnaire correctly through online social media. To test the validity and reliability of the data received, SPES 25.0 software was used, which was then analyzed by Structural Equation Model (SEM) using Amos 23.0 software. The results of statistical data processing show that the strategy of business actors affects success in doing business and affects economic growth but has nothing to do with experience and innovation. The findings of this study have implications for the importance of strategy in dealing with future business to be achieved and successful. The advantage of this research lies in the data collected from questionnaires for Startup owners who experienced business conditions during the Covid-19 pandemic to post-pandemic. The contribution of this research is how startups must prepare business strategies to be successful so that they participate in economic improvement and improvement after the Covid-19 pandemic.